Black Cat. Vol. 18, Guiding light - Yabuki, Kentaro (Viz graphic novel., 2009)
Train and Eve are drawn into a bizarre illusory world controlled solely by the Doctor's warped imagination. Train finds himself confronting doppelgangers of Kyoko and Saya. When the two women that should love him the most try to kill him, Train is left in a terrible predicament.